Comparison of Minimum and Conventional Tillage Systems and Different Nitrogen Doses on Grain Yield of Barley (Hordeum vulgare L) - Kara, Burhan; Mujdeci, Metin (Asian Journal of Chemistry, 2010)
Present study was conducted to evaluate the effects of minimum and conventional tillage systems on yield of barley (Hordeum vulgare L.) under 5 different nitrogen doses. The experiment was a split-plot design with 3 replications and was conducted in irrigated land of Cukurova district in Turkey during 2003 and 2005 growing seasons. Three different tillage systems were tested during this experiment; (1) conventional-till, (2) cultivator and (3) disc-harrow treatments. Along with these 3 tillage systems, nitrogen was added at the rates of 0, 50, 100, 150 and 200 kg N ha-1. Barley variety Kaya was used in the experiment. Results show significant (p ≤ 0.01) differences between the different tillage systems and nitrogen doses. In this study, maximum grain yield was obtained from conventional tillage systems with 200 kg ha-1 nitrogen dose. Results of this experiment show the positive effects from conventional tillage systems and high nitrogen doses for grain yield. It is recommended that barley growing should prefer the conventional tillage systems and 200 kg ha-1 nitrogen dose. It was determined as that the most tillage system were conventional tillage systems and the most nitrogen dose was 200 kg ha-1 for grain yield.